Hubungan Beban Kerja Mental dan Masa Kerja dengan Stres Kerja pada Perawat Instalasi Rawat Inap Rumah Sakit Jiwa Daerah Surakarta - Ria Hesti Utami; Lusi Ismayenti; Rachmawati Prihantina Fauzi (Sekolah Vokasi, Universitas Sebelas Maret, 2025)
Psychiatric inpatient nurses interact directly with psychiatric patients. Nurses need patience and high vigilance. High workload can cause work stress. This study aims to determine the relationship between mental workload and working period with work stress in inpatient nurses at the RSJD Surakarta. The type of research used was analytic observational with cross sectional design. The population amounted to 211 people and after experiencing inclusion and exclusion, the target population was 83 nurses. Sampling using proportionate stratified random sampling technique so that a sample of 75 people. The instruments used were the NASA-TLX questionnaire for the mental workload variable, the questionnaire for the work period variable and the HSE questionnaire for the work stress variable. The analysis technique used Somers'D test and ordinal logistic regression. Somers'D test results show that there is a significant relationship between mental workload and job stress (p=0.001), positive correlation direction, and moderate correlation coefficient (r=0.422). Somers'D correlation test results show that there is a significant relationship between tenure and job stress (p=0.000), negative correlation direction, and moderate correlation coefficient (r=-0.392). Multivariate test results showed that the variable that most influenced the work stress variable was the tenure variable (wald value=14.078). There is a significant correlation between mental workload and working period with work stress in RSJD Surakarta.